2011
DOI: 10.4304/tpls.1.4.400-407
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Learner Output for Enhancing EFL Learners‟ Short-term and Long-term Learning of the English Simple Present Tense

Abstract: Refuting Krashen's Input Hypothesis, some SLA researchers have called attention to the vitality of learner output in the development of their interlanguage systems, which is the essence of Swain's (1985) Output Hypothesis. The present study sought to find out the extent to which elementary EFL learners' output promotes their learning of the English simple present tense. To this end, 33 Iranian EFL learners were assigned into a control and an experimental group. Both groups were presented with three texts inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…input enhancement was effective when it was intensive. Khatib and Bagherkazemi (2011) studied the effect of learners' output on enhancing EFL learners' short-term and long-term learning of simple present tense. The results of the study revealed a trend toward significance within three weeks of experimental period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…input enhancement was effective when it was intensive. Khatib and Bagherkazemi (2011) studied the effect of learners' output on enhancing EFL learners' short-term and long-term learning of simple present tense. The results of the study revealed a trend toward significance within three weeks of experimental period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On their turn, focused communicative drills include storytelling, describing pictures, role playing, conversations, oral presentations, debates and varied writing activities that are carried out to anchor target linguistic forms in EFL learners' minds while delivering authentic meaningful messages (Nassaji & Tian, 2010;Büyükkarci, 2010;Khatib & Bagherkazemi, 2011;Teng, 2017;Mohammadi & Ghaemi, 2022;Marashi & Rezaei, 2023). Therefore, Asadollahfam, Kuhi, Salimi and Mirzaei (2012) and Mirzapour (2016) recommend that EFL learners should be engaged in authentic language production tasks in order to enhance their accurate use of varied linguistic forms.…”
Section: Implicit Fonf Techniquesmentioning
confidence: 99%